2015
DOI: 10.1002/lary.25242
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression demonstrates an immunological capacity of the human endolymphatic sac

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…Møller et al (16) performed a study to investigate gene expression of the human ES using adjacent dura mater as the control. The authors identified that ES was a significant immunological entity within the inner ear.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Møller et al (16) performed a study to investigate gene expression of the human ES using adjacent dura mater as the control. The authors identified that ES was a significant immunological entity within the inner ear.…”
Section: Resultsmentioning
confidence: 99%
“…To further confirm the key genes in ES for AIED, the results were also compared with previous studies by Møller et al (16,17), which investigated the gene expression profile of ES in humans.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the belief that the ES is a significant immunological entity of the inner ear was further enhanced by genetic studies which demonstrated increased expression of key elements of both the cellular and humoral innate immune system, including Toll-like receptors 4 and 7, as well as beta-defensin and lactoferrin [36]. This suggested that not only the ES was capable of antigen recognition and processing for initiation of an immune response, potent molecules directly toxic to invading pathogens were also expressed by the sac epithelium.…”
Section: Discussionmentioning
confidence: 99%